2011
DOI: 10.1016/j.yhbeh.2010.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Social environment affects testosterone level in captive male blue–black grassquits

Abstract: The challenge hypothesis proposes that testosterone (T) elevation above what is needed for breeding is associated with social factors, and males possibly modulate their hormonal response to variations in population density and sex ratio. We investigated the role of social environment in altering testosterone levels and aggression in a tropical, seasonally breeding grassquit (Volatinia jacarina). We exposed males to three social conditions during 1 year: all-males treatment (six males), mixed treatment (three m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…The compositions of the social environment (Lacava et al, 2011;, as well as fish previous social status (Oliveira et al, 2009) and age (Alcazar et al, 2014) have all been shown to affect an animal's physiology and the likelihood of becoming T or NT. Thus, in future studies we must reduce social heterogeneity as much as possible, by placing not only size-matched, but individuals with similar backgrounds and experience.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The compositions of the social environment (Lacava et al, 2011;, as well as fish previous social status (Oliveira et al, 2009) and age (Alcazar et al, 2014) have all been shown to affect an animal's physiology and the likelihood of becoming T or NT. Thus, in future studies we must reduce social heterogeneity as much as possible, by placing not only size-matched, but individuals with similar backgrounds and experience.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…An animal's social environment can have profound effects on its behavior and physiology (Bernhardt et al, 1998;Chu and Wilczynsku, 2001;Galhardo and Oliveira, 2014;Lacava et al, 2011;Mazuc et al, 2003;Pinto et al, 2011;Sessa et al, 2013). Yet, it is not all up to external factors, as individual's internal environment (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…We collected data monthly from all males from August 2007 until July 2008 that included morphometric, plumage coverage as well as spectral and color measures of the plumage (see below). In a parallel study, we also quantified testosterone plasma concentration and aggression levels of males in the mixed and all males treatments to assess the intensity of social competition [50]. Given the associated variation found for testosterone levels with time and the experimental treatments, direct tests of the association of hormonal levels with the phenotypic variables herein measured would be confounded and therefore we restricted ourselves to the discussion of their associated trends.…”
Section: Methodsmentioning
confidence: 99%
“…One reason might be that androgen levels are not only affected by activational and organizational effects (relative plasticity hypothesis) but, moreover, they have also been shown to be modulated by an individual's social environment (Mazur, 1985;Wingfield et al, 1990;Hirschenhauser and Oliveira, 2006;Lacava et al, 2011). Bourgeois males usually defend and monopolize resources (contest competition) to get access to mates and thus face enhanced levels of social challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Oliveira and Oliveira, 2014) such as the biosocial model and the challenge hypothesis, which postulate that androgen profiles are influenced by the current social and reproductive environment (e.g. Goymann, 2009;Lacava et al, 2011;Creel et al, 2013;Almeida et al, 2014). The response in androgen levels of focal males to their social/reproductive environment was tested by exposing bourgeois as well as fixed dwarf males and plastic sneaker males to a different social context, while quantifying their hormonal responses.…”
Section: Introductionmentioning
confidence: 99%